RHINOVIRUS INFECTIONS IN AN ISOLATED ANTARCTIC STATION TRANSMISSION OF THE VIRUSES AND SUSCEPTIBILITY OF THE POPULATION - WARSHAUER, DAVID M.; DICK, ELLIOT C.; MANDEL, ADRIAN D.; FLYNN, TIMOTHY C.; JERDE, RICHARD S. (Oxford University Press, 1989)
It is commonly believed that living in polar isolation causes high susceptibility to respiratory illness. At McMurdo Station, a US research base in Antarctica, we tested this belief by comparing, over 36 days (August 31–October 5, 1976), the incidence and severity of respiratory illness in 64 men finishing six months isolation and in 136 men just arrived from the United States. The colds in the two intermingled populations were essentially equivalent Forty-three per cent of the newcomers and 39% of the wintering group reported colds; symptoms and duration were nearly identical between the two populations. Movement of the colds was slow. The newcomers brought in 31 colds; subsequently, only 52 evenly spaced illnesses arose. Incidence of respiratory illness was twice higher in the smaller living units than in the spacious main dormitory. Two nontypable rhinoviruses, McMurdo 4 and McMurdo 88, were brought in by the new population and were the only viruses isolated. Only McMurdo 88 spread, although more than 85% of the men were antibody-free (<1:3) to either agent McMurdo 88 caused an estimated 60% of antarctic-contracted colds. In brief, this isolated polar group was not especially susceptible to respiratory illness, and virus movement through the group was deliberate